Portfolio Diversification, Leverage, and Financial Contagion - Smith, T. (IMF Working Papers; Working Paper ;, 1999)
Models of 'contagion' rely on market imperfections to explain why adverse shocks in one asset market might be associated with asset sales in many unrelated markets. This paper demonstrates that contagion can be explained with basic portfolio theory without recourse to market imperfections. It also demonstrates that 'Value-at-Risk' portfolio management rules do not have significantly different consequences for portfolio rebalancing and contagion than other rules. The paper's main conclusion is that portfolio diversification and leverage may be sufficient to explain why investors would find it optimal to sell many higher-risk assets when a shock to one asset occurs.